Histological Assessment of Palatal Donor Site Wound Healing after Application of Moringa oleifera Lamarck Leaf Extract in Rats - Amaliya, Amaliya; Muhaimina, Regina Kumala; Susanto, Agus; Sutjiatmo, Afifah B. (European Journal of Dentistry, 2019)
Objective Palatal excisional wound healing in 60 Sprague–Dawley rats was studied for a period of 14 days.Materials and Methods The wounds were made with a punch biopsy instrument with a diameter of 4 mm. After wounding, the test groups received a topical gel of Moringa oleifera Lamarck 2% or 4% leaf extract, whereas control groups received povidone iodine gel and hydroxypropyl methylcellulose (HPMC 4%). Three rats were killed at 0, 3, 7, 10, and 14 days after wounding from each allocated group. The wounds were assessed at different control times and light microscopy was employed to view serial sections from blocks with magnification.Results Histological examination revealed that group treated with M. oleifera Lamarck 4% leaf extract showed the highest fibroblast synthesis and collagen deposition.Conclusion This study suggests that M. oleifera Lamarck leaf extract could be developed as a therapeutic agent for wound healing.
Keywords: open wound; healing; histological assay; Moringa oleifera Lamarck